ANALISIS PENDAPATAN DAN KELAYAKAN USAHA KOPI EXTRACT.CO DITINJAU DARI ASPEK FINANSIAL DI KECAMATAN SUKAJADI PEKANBARU - Murnawati, Murnawati; Erti, Lili; Tasril, Tasril; Hakim, Aditiya; Asmawi, Rohim (Komunitas Manajemen Kompetitif, 2024)
Currently, the coffee business or business, especially in the Sukajadi sub-district, is growing rapidly, many entrepreneurs are emerging who are opening cafe businesses with various concepts and ideas designed to attract customers from various circles. This research uses a descriptive method, with a survey approach, using secondary data. The population and sample in this research are financial reports and information from the leadership and employees of Kopi Exract. Co in Sukajadi sub-district, Pekanbaru city, there are 7 people The aim of this research is to determine and analyze the income and feasibility of the business using several methods, to see the amount of profit using Cash Flow. Pay back Period, Provitabily Index, Net Present Value (NPV) Average Rate of Return (ARR), Internal Rate of Return (IRR), The research results, based on income analysis, provide greater benefits compared to the costs incurred, while to see the feasibility of using investment criteria, namely the Payback period (PP) method, the investment has been returned for 2 years, 2 months 8 days, the Average Rete method of Return (ARR), the average profit obtained each year is 40.91%, with the Net Present Value (NPV) method producing a positive value of IDR 182,139,243,- with a discount factor level of 15% (NPV>0), for provitability index method, looking at the comparison of the present value of net income compared to investment expenditure, 1.56% has a positive value (PI > 1) for calculating the Internal Rate of Return (IRR), a value of 38.92% > 15% is obtained, so that the investment invested in The Extract.Co Coffee business is worth running and developing Kata kunci : Pendapatan,, Kelayakan Financial, Kopi Exract.Co